Metodologia, Sistema de Codificação e Ferramenta de software para Modelagem de Móveis Modulados - Carvalho, Viviane Maria Lélis (2010)
On this research we investigated how new technologies can help the process of design and manufacturing of furniture in such small manufacturers in Rio Grande do Norte state. Google SketchUp, a 3D software tool, was developed in such a way that its internal structures are opened and can be accessed using SketchUp s API for Ruby and programs written in Ruby language (plugins). Using the concepts of the so-called Group Technology and the flexibility that enables adding new functionalities to this software, it was created a Methodology for Modeling of Furniture, a Coding System and a plugin for Google s tool in order to implement the Methodology developed. As resulted, the following facilities are available: the user may create and reuse the library s models over-and-over; reports of the materials manufacturing process costs are provided and, finally, detailed drawings, getting a better integration between the furniture design and manufacturing process